Selection of key sustainable indicators to steel buildings in early design phases - Andrade, Joana B. (2012)
The construction industry attempts to produce buildings with the least possible environmental impact. However, construction activities still greatly impacting the environment; therefore, it is necessary to consider a sustainable project approach, based on its performance. Sustainability is an important issue to consider in design, due to environmental concerns and economic and social issues, promoting the architectural quality and economic advantages. This paper aims to identify the phases that a design project should pass through, emphasising the importance and ability of earlier ones to influence the level of sustainability, performance and life cost over project life. Then one intends to select a set of sustainability indicators, based on a pre-set list, predicting its adaptability to the conceptual and pre-design phases under steel buildings. The output of this paper is aimed to aid the development of a tool/concepts that would enable designers to compare and evaluate the consequences of different design solutions, based on preliminary data and facilitate the collaboration between various partners and client and eventually yield a sustainable and high performance building through its life cycle.